DETERMINAN LOYALITAS MAHASISWA - Wardati, Emi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This study examines the effect of determinant factors of student loyalty. Population in this study were students in STIE Totalwin Semarang. Based on purposive sampling method, 240 samples were obtained by observation data. The results of this study indicate that students satisfaction, students trust, students commitment, and students perception about learning has significant influence on student loyalty